Do wetlands enhance downstream denitrification in agricultural landscapes?. Issue 10 (19th October 2016) - Hansen, Amy T.; Dolph, Christine L.; Finlay, Jacques C.
Abstract: Wetlands are known to be effective sinks for nitrate. Wetland restoration and construction have gained traction as viable conservation measures to improve water quality in intensively managed agricultural landscapes. In addition to reducing nitrate in situ, wetlands may have impacts on water chemistry and temperature dynamics that extend beyond the confines of the wetlands themselves. Nonsaturating nitrate concentrations (NO3 − ), enhanced organic carbon effluxes, and altered temperature dynamics in streams downstream of wetlands could all affect denitrification rates within a stream network, potentially extending water quality benefits beyond wetland boundaries. We investigated the effect of wetlands on water chemistry, water temperature, and benthic denitrification rates in downstream agricultural ditches through a field measurement campaign over the open water season. We found that although ditches located downstream of wetlands had lower NO3 − and higher DOC, ditch denitrification rate was not significantly altered by the presence of upstream wetlands. Rather, wetlands indirectly affected denitrification within ditches by strongly influencing the stoichiometry of the two limiting resources, NO3 − and organic carbon. Peak denitrification rates in ditches were observed when DOC and NO3 − supplies were approximately balanced, that is, at DOC: NO3 − ratios that were near the microbial requirement for denitrification. NO3 − limitation occurred primarily at sites with >3% wetland cover, and in the fall season at all sites, and DOC limitation occurred primarily at sites with <1% wetland cover. Temperature was found to be a secondary control that was important only when NO3 − and DOC availabilities were balanced. Our results suggest that wetland restoration and construction targeting nitrate reduction within intensively agriculturally managed basins should be implemented in a way that promotes balanced resource availability throughout fluvial networks. Wetlands are an important regulator of resource availability and thus could be used to create conditions that maximize denitrification in NO3 − ‐enriched watersheds.